Model of Javelin Throwing Learning for SMK Students - Ana Laela; Samsuddin Samsuddin; Hernawan Hernawan (Universitas Negeri Medan, 2020)
The aim of the study was to produce and develop a javelin learning model for SMK students. This research uses the method of Research and Development (R&D) of Borg and Gall, the subject of this research and development is the student/I SMK Negeri 2 Rangkas Bitung. In limited trials (small group trials) use subjects 20 students/I and a large group trial using 40 subjects while the effectiveness test was using the 40 subjects. In the test of the effectiveness of learning models using the instrument assessment instruments how to hold the javelin, prefix attitude, throwing movements, the final attitude/recovery using rubric/portfolio (Process Assessment). Analysis of the data in this study using test-T, the results of the initial test before given the treatment of a javelin learning model amounting to 52.93 then after giving the treatment of the learning model in javelin increased to 89.90. In the test of significance differences with application. Keywords: Learning Model, javelin throw